Effect of ischemic preconditioning on cardiovascular outcomes in patients with symptomatic coronary artery disease: a cohort study. Issue 7 (November 2019) - Rahmi, Rosa M.; Hueb, Whady; Rezende, Paulo C.; Garzillo, Cibele L.; Uchida, Augusto H.; Scudeler, Thiago L.; Ramires, José A.F.; Filho, Roberto K.
Abstract : Background: Despite the powerful myocardial protection of ischemic preconditioning (IP) observed in experimental studies, it remains a challenge to observe such protection in humans. Thus, the aim of this study was to evaluate the possible effects of IP on clinical outcomes in patients with coronary artery disease (CAD). Patients and methods: In this cohort study, patients with multivessel CAD, preserved systolic ventricular function, and stable angina were prospectively selected. They underwent two sequential exercise stress tests (EST) to evaluate IP presence. IP was considered present if patients had an improvement in the time to the onset of 1.0-mm STsegment deviation in the second EST. The primary end point was the composite rate of cardiac death, nonfatal myocardial infarction, or revascularization during 1-year follow-up. Patients with (IP+) and without (IP−) the cardioprotective mechanism were compared regarding clinical end points. Results: A total of 229 patients completed EST and had IP evaluated: 165 (72%) were IP+ and 64 (28%) were IP − patients. Of these, 218 patients had complete follow-up. At 1-year, event-free survival regarding the primary end point was 95.5 versus 83.6% ( P = 0.0024) and event-free survival regarding cardiac death or myocardial infarction was 99.4 versus 91.7% (P=0.0020), respectively, in IP + and IP − groups. The unadjusted hazard ratio (IP + /IP−) for the primary end point was 4.63 (1.52–14.08). After multivariate analysis, IP was still significantly associated with better clinical outcomes ( P = 0.0025). Conclusion: This data suggest that IP may contribute to better clinical outcomes in patients with ischemic heart disease.